(untitled) (Fiep Bulletin - online, 2015)
One of the crucial factors for the success when dealing with health is the assessment done before the beginning of a physical activity. It allows one to know about people as a whole so that he can have consistent data so as to prescribe a physical training. With the increasing search for a better quality of life by people anywhere, gym clubs are investing in qualified professionals to work in this area. Thus, the aim of this study is to investigate the importance of physical assessment according to gym clubs instructors in Rio de Janeiro city through a questionnaire with 11 objective questions. Based on the results, we conclude that gym clubs should demand physical assessment as well as a re-assessment for programs in gym and weight training activities both carried on by qualified professionals so that it can be safely and scientifically done and enable one to prescribe right exercises in a safe way for practioners.